Electronic payment as a tool for the discharge of monetary obligations in the virtual environment: A comparative study - ALLAOUA, Ait Amira Anaghim; AMOURA, Amira (The International tax journal, 2026)
With the accelerated digital transformation, electronic payment has become an essential means for the discharge of monetary obligations, replacing paper currency and checks in numerous transactions. This system offers speed, efficiency, and ease of tracking operations. However, it raises significant legal issues concerning the legitimacy of electronic means, the evidentiary value of digital records in proof, as well as data protection and transaction security. In Libya, this field is regulated by Law No. 6 of 2022 on Electronic Transactions, while in Algeria, it is governed by Law No. 15-04 on Electronic Signatures, Law No. 73-59 (as amended by Law No. 05-02), Law No. 03-11 on Currency and Credit, and Law No. 18-05 on Electronic Commerce. Electronic payment methods include bank cards, electronic checks, transfers, electronic money, and electronic wallets. These methods face multiple risks, most notably hacking, fraud, unauthorized use of cards, and weaknesses in systems or their design. To address these, reliance is placed on technical and legal safeguards such as securing electronic websites, legally recognized electronic signatures, and encryption to protect data confidentiality, prevent tampering, and ensure the validity of transactions.